Disolución e invención: ficciones críticas en Saer y Aira - David Parra Miranda (Cuadernos LIRICO)
The works of Saer and Aira create a chiasmatic intersection between fiction and critique: their fictions interfere with the diegetic conventions of the narrative genre while simultaneously redefining the creative possibilities of critique. In Aira's case, it is a vast fictional diary of imaginations and speculations that claim their own status of reality. In Saer's work, the speculative descriptive edge of his narratives, or “imaginary treatises,” dissolves the field of fictions fixed by society. In both cases, these are critical devices that disorient our “phantasmal mechanisms” and endow a new depth to both the status of fiction and that of critique. It is proposed to read these exercises from their respective ethics: dissolution and invention.fiction, critique, narrative, invention, dissolution